HISTORICAL SCIENCE DURING THE REIGN OF SULTAN HUSAIN MIRZO AND THE HERAT SCHOOL OF HISTORIOGRAPHY - Sherzod Jo‘rayev (International Journal of Literature and Language Studies, 2026)
The article analyzes how historiography in the scholarly-cultural milieu of Herat reached a new qualitative and substantive stage during the reign of Sultan Husayn Mirza. Owing to Alisher Navoi’s direct patronage and scholarly-educational initiatives, the works of Mirkhwand, Khwandamir, Kamoliddin Abdurazzoq Samarqandi, Davlatshoh Samarqandi, and Zayniddin Vosiﬁ consolidated source-based analysis, comparative approaches, and methods for identifying causal relationships. The study outlines the content and features of Ravzat us-safo, Habib us-siyar, Matlaʿ as-saʿdayn va majmaʿ al-bahrayn, Tazkirat ush-shuaro, Badoyiʿ al-vaqoyiʿ, as well as Navoi’s Tarixi anbiyo va hukamo and Tarixi mulki Ajam. The authors harmonize traditional Islamic worldviews with historical narration, expanding the evidentiary base, conducting cross-comparisons, and synthesizing conclusions to present history as a coherent, internally logical whole. The Herat school, in turn, exerted a strong influence on the historical-literary traditions of Turan in subsequent centuries.